Geographical Routing Problem of Wireless Sensor Networks with Multiple Mobile Sinks - SABRI, Yassine (International Journal of Computer Sciences and Engineering, 2025)
In this study, the problem of building Level-based topologies for Wireless Sensor Networks with several sinks is considered. The optimization relies on different levels of decision: choosing which sensors are masters and balancing the load among sinks, in order to prolong the network life time and improve its scalability. In this paper we present an enhancement to the GRPW algorithm for wireless sensor networks. Performance of GRPW algorithm depends heavily on single sink position , we propose a protocol based on Multiple Static Sinks, we modified the existing sink location privacy protection scheme by dividing nodes in the network containing multiple sink into different levels in which real packets are forwarded to sink belong to corresponding logical levels and the intermediate node generating fake packets and sending it to fake sinks. Using OMNET++ simulation and the MiXiM framework, it is shown that proposed protocol significantly improves the robustness and adapts to rapid topological changes with multiple sinks, while efficiently reducing the communication overhead and the energy consumption .